Local IFNα enhances the anti-tumoral efficacy of systemic anti-PD1 to prevent tumor relapse - Maxime Thoreau; Fabienne Regnier; Ludger Johannes; Estelle Dransart; Alain Trautmann; Nadege Bercovici; Marion v Guerin; Lene Vimeux; Matthieu Benard; Hweixian L Penny (Journal for ImmunoTherapy of Cancer)
Background Tumor relapse constitutes a major challenge for anti-tumoral treatments, including immunotherapies. Indeed, most cancer-related deaths occur during the tumor relapse phase.Methods We designed a mouse model of tumor relapse in which mice transplanted with E7+ TC1 tumor cells received a single therapeutic vaccination of STxB-E7+IFNα. Unlike the complete regression observed after two vaccinations, such a treatment induced a transient shrinkage of the tumor mass, followed by a rapid tumor outgrowth. To prevent this relapse, we tested the efficacy of a local administration of IFNα together with a systemic therapy with anti-PD1 Ab. The immune response was analyzed during both the tumor regression and relapse phases.Results We show that, during the regression phase, tumors of mice treated with a single vaccination of STxB-E7 + IFNα harbor fewer activated CD8 T cells and monocytes than tumors doomed to fully regress after two vaccinations. In contrast, the systemic injection of an anti-PD1 Ab combined with the peri-tumoral injection of IFNα in this time frame promotes infiltration of activated CD8 T cells and myeloid cells, which, together, exert a high cytotoxicity in vitro against TC1 cells. Moreover, the IFNα and anti-PD1 Ab combination was found to be more efficient than IFNα or anti-PD1 used alone in preventing tumor relapse and was better able to prolong mice survival.Conclusions Together, these results indicate that the local increase of IFNα in combination with an anti-PD1 therapy is an effective way to promote efficient and durable innate and adaptive immune responses preventing tumor relapse.